Pengaruh Pendanaan Iklim terhadap Penurunan Emisi Karbon melalui Energi Terbarukan di Indonesia - Evitasari, Noviani; Komarulzaman, Ahmad (Jurnal Ekonomi dan Pembangunan Indonesia, 2023)
Climate change causes various negative impacts on life, thus requiring mitigation and adaptation actions. Climate finance could support the transition to a low-carbon economy globally, including in Indonesia. However, empirical research on climate finance in Indonesia is still limited. This study uses path analysis to examine the relationship between climate finance, renewable energy mix, and carbon emissions in Indonesia from 1973 to 2020. The results show that climate finance could not directly reduce carbon emissions or promote renewable energy indirectly. These findings indicate the need to reallocate climate finance to sectors that have the potential to reduce carbon in Indonesia.